2003
DOI: 10.1088/0960-1317/14/1/304
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the flow characteristics within a micronozzle/diffuser

Abstract: In this paper, we present an analysis of the performance of micronozzle/diffusers and we report on the fabrication and testing of a micronozzle/diffuser. We have found that the pressure loss coefficient for the nozzle/diffuser decreases with the Reynolds number. At a given Reynolds number, the pressure loss coefficient for the nozzle is higher than that of the diffuser due to a considerable difference in the momentum change. We find that the nozzle/diffuser length has little influence on the pressure loss coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…They observed that flow rectification through the diffusernozzle element is possible for very low Reynolds number laminar flows. Experimental investigations of the performance of diffuser-nozzle elements were performed by Yang et al (2004). They found that the pressure loss coefficients of the nozzle and diffuser decreased as the Reynolds number was decreased, resulting in an increased rectification capability.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that flow rectification through the diffusernozzle element is possible for very low Reynolds number laminar flows. Experimental investigations of the performance of diffuser-nozzle elements were performed by Yang et al (2004). They found that the pressure loss coefficients of the nozzle and diffuser decreased as the Reynolds number was decreased, resulting in an increased rectification capability.…”
Section: Introductionmentioning
confidence: 99%
“…It is due to the efficiency ratio of conventional micro nozzle/diffuser significantly increases with the Reynolds number. In conventional micro nozzle/diffuser, the loss coefficient for the nozzle at the exit is higher due to free jet flow accompanied with some additional pressure recovery for diffuser, leading to a higher efficiency at the higher Reynolds number region (Yang et al 2004). Accordingly in higher flow velocity region, the added enhancements reduce the influence of the above-mentioned two factors, thereby resulting in a lower efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, normally the loss coefficient of diffuser is less than that of nozzle, hence more fluid flow rate through the diffuser than the nozzle is expected at the same pressure drop across both elements. However, the published literature about the micro nozzle/diffuser is mainly focused on the manufacturing technology as well as its performance (Yang et al 2004;Chen et al 2008) or simulating the performance of micropump with micro nozzle/diffuser valve (Yang et al 2006(Yang et al , 2008. Despite its simple and robust nature, the nozzle/ diffuser micropump suffers from low efficiency.…”
mentioning
confidence: 99%
“…The relationship between Q and η was indicated in equation (2). If η>1, then Q>0, the fluid will enter the pump cavity from the inlet and pump out from the outlet, hence the net flow is formed from inlet to outlet.…”
Section: Fig 1 Sem Of Micro Diffuser/nozzle With Flat Wall � the Difmentioning
confidence: 99%
“…As diffuser/nozzles are the key parts, many research jobs have been focused on optimizing its physical dimension [2,3] and developing micro fabrication technology [4] for µTAS application.…”
Section: Introductionmentioning
confidence: 99%